2016
DOI: 10.1097/psy.0000000000000344
|View full text |Cite
|
Sign up to set email alerts
|

Associations Among Child Abuse, Depression, and Interleukin-6 in Pregnant Adolescents: Paradoxical Findings

Abstract: Objective Limited data exist on child abuse-related immune variation during pregnancy, despite implications for maternal and infant health and extensive data showing that abuse history and depression are related to increased inflammation in other populations. This study examined associations among child abuse, depression, circulating levels of inflammatory markers, and perinatal health in pregnant adolescents, a group at high risk for childhood abuse and poor birth outcomes. Methods Pregnant teenagers (n=133… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 66 publications
1
36
0
Order By: Relevance
“…Consistent with the larger literature (Miller et al, 2017; Mitchell et al, 2018; Walsh et al, 2016), the current study provides further evidence that adversities experienced during childhood and adulthood are associated with elevated inflammatory markers during pregnancy. Specifically, bivariate correlations revealed that a history of childhood abuse was positively associated with both CRP and IL-6 in a sample of pregnant women, while current SES was negatively associated with both CRP and IL-6.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the larger literature (Miller et al, 2017; Mitchell et al, 2018; Walsh et al, 2016), the current study provides further evidence that adversities experienced during childhood and adulthood are associated with elevated inflammatory markers during pregnancy. Specifically, bivariate correlations revealed that a history of childhood abuse was positively associated with both CRP and IL-6 in a sample of pregnant women, while current SES was negatively associated with both CRP and IL-6.…”
Section: Discussionsupporting
confidence: 90%
“…The articles presented in this review evaluated sexual abuse as an independent variable alone or a subtype of childhood maltreatment (CM), in this case the authors investigated other types of abuse besides CSA, making correlations between the inflammatory markers and each type of abuse, including CSA. Only two studies evaluated exclusively CSA ( 37 , 48 ), other two data investigated physical and sexual abuse ( 38 , 51 ), the remain 13 studies evaluated all subtypes of maltreatment and the correlation of each subtype, and CM global scores, to immune system alterations ( 39 47 , 49 , 50 , 52 , 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies ( 39 , 40 , 42 , 44 47 , 52 , 53 ) used the Childhood Trauma Questionnaire (CTQ), a self-applicable instrument used for assessing physical, emotional, sexual abuses as well as physical and emotional negligence ( 54 ). The items are added up so that the five different subtypes of abuse score differently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, one study has shown that regulatory T-cells are significantly increased in both the prenatal and postnatal period in mothers suffering depression 190 . Another study has shown that experience of abuse may be the key moderator of this relationship, as experience of abuse and depression in pregnant adolescents predicts higher IL-6 concentration during pregnancy, but none such association in absence of exposure to abuse 203 . However, other studies investigating cytokine levels have shown that depressive symptoms during pregnancy are negatively correlated with cytokines such as IL-1β, Il-7 and TNFa 204,205 .…”
Section: Immune Systemmentioning
confidence: 99%